Climatic characteristics of various tracks of tropical cyclones and their impact on rainfall in Qingdao during 1949–2020 - Ma, Yan; Guo, Lina; Hao, Yan (Frontiers in Climate, 2024)
The climatic characteristics of tropical cyclones affecting Qingdao, China, were analyzed from the aspects of frequency, period, and intensity of the tropical cyclones and their impact on rainfall in Qingdao by referring to the Typhoon Yearbook, the tropical cyclone data of China during 1949-2020 as well as surface meteorological observations . The results showed that the frequency of tropical cyclones affecting Qingdao during 1949-2020 took on an overall decreasing trend and mostly exhibited a significant variation period of 2-4 year.Tropical cyclones with the track of turning after landfall and continuing northward after landfall accounted for 47.9%. In July, there were tropical cyclones mainly followed tracks of continuing northward after landfall, and tracks turning after landfall mostly occurred in September. The intensity of the tropical cyclones showed an overall weakening feature with distinct inter-decadal variations, and it did not change much when the northward tropical cyclones close affecting Qingdao. The different track of tropical cyclones had spatially heterogeneous, strong rainfall in Qingdao with the track of continuing northward after landfall brought the highest daily and process rainfall to Qingdao, while the tropical cyclones turning nearshore or advancing offshore before landfall had relatively little rainfall.